The dynamic influence of subsurface geological processes on the assembly and diversification of thermophilic microbial communities in continental hydrothermal systems - Kenneth W.W. Sims; Cole M. Messa; Sean R. Scott; Andrew D. Parsekian; Andrew Miller; Abraham L. Role; Timothy P. Moloney; Everett L. Shock; Jacob B. Lowenstern; R. Blaine McCleskey; Matthew A. Charette; Bradley J. Carr; et al. (Geochimica et Cosmochimica Acta, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

BEMMA: A Hierarchical Bayesian End-Member Modeling Analysis of Sediment Grain-Size Distributions - Shi-Yong Yu; Steven M. Colman; Linxiong Li (Mathematical Geosciences, 2016)

Abrupt deglaciation on the northeastern Tibetan Plateau: evidence from Lake Qinghai - Xiuju Liu; Steven M. Colman; Erik T. Brown; Andrew C. G. Henderson; Josef P. Werne; Jonathan A. Holmes (Journal of Paleolimnology, 2014)

Estimation of carbonate, total organic carbon, and biogenic silica content by FTIR and XRF techniques in lacustrine sediments - Xiuju Liu; Steven M. Colman; Erik T. Brown; Elizabeth C. Minor; Hongyu Li (Journal of Paleolimnology, 2013)

Post-Marquette discharge from Glacial Lake Agassiz into the Superior basin - Jessica L. Gary; Steven M. Colman; Nigel J. Wattrus; C. F. M. Lewis (Journal of Paleolimnology, 2012)

Determining the spatial and temporal patterns of climate changes in China's western interior during the last 15 ka from lacustrine oxygen isotope records - Shi‐Yong Yu; Richard D. Ricketts; Steven M. Colman (Journal of Quaternary Science, 2009)
China's western interior is a climatologically complex region, where climatic conditions are primarily controlled by the westerly jet stream and the Asian monsoon system. Observations reveal that the δ 18 O signatures of these atmospheric elements as expressed in their meteoric waters are different, and these differences are reflected in the lacustrine systems that are ultimately fed by the meteoric waters. Empirical orthogonal function (EOF) decomposition of 17 lacustrine δ 18 O records from this area clearly reveals the spatial and temporal structures of climate changes during the last 15 ka. The first EOF mode, dominated by sites in the NW sector, captures the temperature effect on the variability of the δ 18 O dataset. We interpret the variations through time in the amplitude of this mode to be indicative of changes in summer air temperature. The second EOF mode, heavily weighted by sites in the SE sector, reveals the ‘amount effect’ on δ 18 O, and thus its amplitude time series indicates changes in the intensity of the Asian summer monsoon. Our EOF‐based reconstructions of regional climate are generally consistent with the δ 18 O records of ice cores, cave speleothems and marine carbonates. Copyright © 2008 John Wiley & Sons, Ltd.

Paleolimnology and Paleoclimate Studies in Upper Klamath Lake, Oregon - Steven M. Colman; J. Platt Bradbury; Joseph G. Rosenbaum (Journal of Paleolimnology, 2004)

Chronology of Sediment Deposition in Upper Klamath Lake, Oregon - Steven M. Colman; J. Platt Bradbury; John P. McGeehin; Charles W. Holmes; David Edginton; Andrei M. Sarna-Wojcicki (Journal of Paleolimnology, 2004)

The History of Recent Limnological Changes and Human Impact on Upper Klamath Lake, Oregon - J. Platt Bradbury; Steven M. Colman; Richard L. Reynolds (Journal of Paleolimnology, 2004)

Limnological and Climatic Environments at Upper Klamath Lake, Oregon during the past 45 000 years - J. Platt Bradbury; Steven M. Colman; Walter E. Dean (Journal of Paleolimnology, 2004)

Paleolimnology of Lake Tanganyika, East Africa, over the past 100 kyr - Christopher A. Scholz; John W. King; Geoffrey S. Ellis; Peter K. Swart; J. Curt Stager; Steven M. Colman (Journal of Paleolimnology, 2003)

Birth of the modern Chesapeake Bay estuary between 7.4 and 8.2 ka and implications for global sea-level rise - John F. Bratton; Steven M. Colman; E. Robert Thieler; Robert R. Seal (Geo-Marine Letters, 2002)

Biogenic silica from the BDP93 drill site and adjacent areas of the Selenga Delta, Lake Baikal, Siberia - Steven M. Colman; John A. Peck; Josephine Hatton; Eugene B. Karabanov; John W. King (Journal of Paleolimnology, 1999)